2017
DOI: 10.1016/j.forsciint.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into artefacts formed during gas chromatography/mass spectrometry analysis of firearms propellant that contains diphenylamine as the stabiliser

Abstract: Highlights Identification of artefacts formed during gas chromatography analysis of firearms propellant.  Identification of a previously unreported diphenylamine derivative.  Identity of artefact confirmed by synthesis. ABSTRACTIn the course of providing assistance to legal counsel in a matter that involved the analysis of firearms propellant by gas chromatography/mass spectrometry it was noticed that phenoxazine was reported as a component of 0.22 calibre propellant that contained diphenylamine as the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They found that adhesive tape, which is the typical collection method for IGSR, collected the most OGSR in comparison to the other substrates. Pigou et al performed a study using GC/MS which investigated the potential formation of artifacts during the analysis of propellant from ammunition cartridges . They found that the formation of artifacts was possible and stated that while these artifacts do not interfere with identifying propellant conclusively, such artifact formation could lead to problems when trying to correlate the analyzed sample to a reference sample.…”
Section: Gunshot Residuementioning
confidence: 99%
“…They found that adhesive tape, which is the typical collection method for IGSR, collected the most OGSR in comparison to the other substrates. Pigou et al performed a study using GC/MS which investigated the potential formation of artifacts during the analysis of propellant from ammunition cartridges . They found that the formation of artifacts was possible and stated that while these artifacts do not interfere with identifying propellant conclusively, such artifact formation could lead to problems when trying to correlate the analyzed sample to a reference sample.…”
Section: Gunshot Residuementioning
confidence: 99%
“…Mass spectra of diphenylamine are commonly reported in the literature (calcd m / z 170.0969). Using the DSA-ToF, DPA exhibited simple ionization behavior in positive-ion mode, with a single peak for the protonated molecular ion very much dominating the spectra (meas m / z 170.0970, n = 5, Δppm +0.57). DPA is also known to produce a fragment ion at m / z ∼92, assigned to [C 6 H 5 NH] + , resulting from the loss of a benzyl moiety from the protonated parent.…”
Section: Resultsmentioning
confidence: 96%
“…Further, calibration of DPA using this technique showed wide range linear response (100-5000 mg L À 1 ) and hence, DPA can be detected over a wide range of concentration in propellant samples. By using GC-MS technique, the contamination of the inlet liner and any artefact formation in the firearm propellant containing DPA or others was monitored [17]. Quantitative detection of stabilizer like DPA, DPA-derivative, centralite in gunpowder was done by HP-TLC by comparing the positions of peaks and the quantitative estimation was done by comparing the area of the spot with the standard [18].…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…By using GC‐MS technique, the contamination of the inlet liner and any artefact formation in the firearm propellant containing DPA or others was monitored [17]. Quantitative detection of stabilizer like DPA, DPA‐derivative, centralite in gunpowder was done by HP‐TLC by comparing the positions of peaks and the quantitative estimation was done by comparing the area of the spot with the standard [18].…”
Section: Chromatographic Methodsmentioning
confidence: 99%